CHARACTERIZATION OF SPECIFIC HEAT CAPACITY OF WATER-ALUMINUM OXIDE-BASED NANOFLUIDS - Waluyo, Roy; Deendarlianto, Deendarlianto; Indarto, Indarto; Yuliaji, Dwi; Kharisma, Sunandi; Maryadi , Shendy Akbar; Oktaviandi, Ryan; Juarsa, Mulya (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
Since the advent of nanofluids, engineers have expected major gains in thermal‐system efficiency. Yet a key property—specific heat capacity (Cp)—remains poorly understood, because Cp is not a single value but a spectrum governed by nanoparticle size, shape, material, and concentration. Deeper insight is essential, especially for natural‑circulation experiments that rely on accurately characterized working fluids. This study targets that gap by measuring the Cp of Al₂O₃–water nanofluids at mass fractions of 0.1, 0.2, and 0.3 wt%. Thirty-nanometer Al₂O₃ particles were dispersed in deionized water using magnetic stirring and ultrasonic processing. The nanofluid was heated in a thermostatic bath while temperature rise was tracked with thermocouples and a data‑acquisition system. Results reveal that relative Cp decreases as nanoparticle concentration increases and is also sensitive to fluid temperature. These findings clarify how concentration and temperature jointly shape the thermal behavior of Al₂O₃ nanofluids, guiding for design high‑performance natural‑circulation loops and other heat‑transfer applications.